(untitled) (Journal of Hama University, 2024)
If this proves to be the Holy Quran miraculous proved to be an argument on all who believed in him who Have the components of commissioning of humans, and therefore they cannot afford turning away from him or ignore anything of his principles and provisions, it is inevitable for them to demand it, and reflect on, and then undergo each of the contents of orders and prohibitions . for this reason this research was a contribution to the construction of knowledge of this art from the Islamic Shari’a Sciences, By exposing unveils a existence miracles in the curriculum of the Holy Quran in a statement of jurisprudential provisions; the importance that each interpreter and fundamentalist jurist and in the understanding of the Quranic text and devise judgment idiosyncratic him properly, because knowing that instructs to cause around which the referee idiosyncratic, as well as to the wisdom and the Supreme purpose legislation jurisprudence process In order for the research to achieve the desired goal, the committee dealt with the inductive and analytical approach, within eight chapters in the statement of jurisprudential that the divine legislation has many miraculous faces, and the style of the Qur’an in rulings is considered one of the foundations among the most important findings of the research: that the divine legislation has many miraculous faces, and the style of the Qur’an in explaining jurisprudential rulings is one of these faces and that knowledge of the principles that help in understanding the Qur’anic text, and that one of the most important purposes of the diversity of the Qur’anic style in explanation of rulings: a statement of the legislative wisdom of the ruling, a statement of the reason for the ruling with which it revolves whether or not it exists, and a statement of the validity of divine